2017
DOI: 10.1088/1475-7516/2017/12/017
|View full text |Cite
|
Sign up to set email alerts
|

High-energy gamma rays and neutrinos from nearby radio galaxies

Abstract: Abstract. Multi-messenger data suggest that radio galaxies (i.e. non-blazar active galaxies) are a well-motivated class of sources for the diffuse flux of high-energy neutrinos reported by the IceCube Collaboration. In this study, we consider the gamma-ray spectrum observed from four nearby radio galaxies (Centaurus A, PKS 0625-35, NGC 1275 and IC 310) and constrain the intensity and spectral shape of the emission injected from these sources, accounting for the effects of attenuation and contributions from ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 149 publications
(242 reference statements)
0
19
0
Order By: Relevance
“…The spectrum and trajectory of very high-energy gamma rays propagating through radiation and magnetic fields is continuously shaped by the production and development of electromagnetic cascades [69][70][71][72][73][74]. In this section, we describe these gamma-ray induced cascades and their impact on indirect searches for very heavy dark matter particles.…”
Section: Gamma-ray Attenuation and Electromagnetic Cascadesmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum and trajectory of very high-energy gamma rays propagating through radiation and magnetic fields is continuously shaped by the production and development of electromagnetic cascades [69][70][71][72][73][74]. In this section, we describe these gamma-ray induced cascades and their impact on indirect searches for very heavy dark matter particles.…”
Section: Gamma-ray Attenuation and Electromagnetic Cascadesmentioning
confidence: 99%
“…3.1 and following the procedure described in Ref. [69]. Pair production within Virgo is again dominated by scattering with the CMB (the energy densities in the infrared, optical, and ultraviolet radiation fields within Virgo are approximately two orders of magnitude lower than that of the CMB [99]).…”
Section: Gamma-rays From Dwarf Galaxiesmentioning
confidence: 99%
“…So far, a coincident detection between a high-energy neutrino and any known GRB has not been found (Achterberg et al 2008;). Starburst galaxies and other types of AGN such as radio-quiet quasars (Stecker & Salamon 1996;Alvarez-Muñiz & Mészáros 2004), low luminosity AGN (LLAGN) (Kimura et al 2015) or radio galaxies (Becker Tjus et al 2014;Hooper 2016;Blanco & Hooper 2017) remain potential candidates for the observed diffuse neutrino flux.…”
Section: Introductionmentioning
confidence: 99%
“…The analyisis presented here is developed under the AMON framework. The purpose of the this analysis is to search for transient or variable sources that can produce both gamma rays and neutrinos, specially sources like blazars or radio galaxies [7].…”
Section: Introductionmentioning
confidence: 99%